PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN WARD AND PEPPER (Studi kasus Dinas Perpustakaan dan Kearsipan Salatiga) - Askar Wirawan; Augie David Manuputty (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Regional Library and Archives Office of Salatiga is one of the government offices which works actively in the use of information systems and information technology in implementing business processes to run efficiently. To keep business processes running efficiently, strategic planning of information systems is needed. This study uses a qualitative approach with the framework of Ward and Peppard (2002). These stages consist of data collection, analysis process, and the output. The data collection stage contains a description of the internal business environment condition, the condition of the external business environment, the condition of the organization's internal information system and the condition of the organization's external information system. Several analytical methods such as SWOT Analysis, CSF are used to analyze the internal and external business environment. The results of this research are IS/IT strategic plans and IS/IT blueprints which will be used as the references in developing IS/IT in Regional Libraries and Archives Office of Salatiga in the future.